Plasma myeloperoxidase interactions with cadmium, lead, arsenic, and selenium and their impact on chronic kidney disease - Hsi-Hsien Chen; Ya-Li Huang; Chih-Yin Wu; Mei-Chieh Chen; Horng-Sheng Shiue; Sheng-Lun Hsu; Ying-Chin Lin; Yu-Mei Hsueh (Ecotoxicology and Environmental Safety)
Myeloperoxidase (MPO) is an oxidative stress biomarker, with elevated MPO levels linked to chronic kidney disease (CKD) progression. Metal exposure is a risk factor for CKD, and is also correlated to MPO expression, with specific MPO genotypes linked to MPO expression. Therefore, we examined whether MPO plasma levels or MPO polymorphisms were linked to CKD, and explored whether these factors modified associations between CKD and metal concentrations. Accordingly, we recruited 395 age- and sex-matched controls and 215 patients with CKD (persistent estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73 m2 for a minimum of 12 weeks without hemodialysis). We identified no associations between several MPO genotypes and CKD. However, after multivariate adjustment, plasma MPO concentrations were positively correlated with CKD odds ratio (OR) = 5.87 (95 % confidence interval [CI]: 3.14–10.96). Significant additive interactions were observed between high plasma MPO concentrations and elevated blood cadmium (Cd) and lead (Pb) levels, and total urinary arsenic (As), or low plasma selenium (Se) concentrations, leading to increased ORs for CKD, with significant synergy indices recorded. High plasma MPO concentrations also showed multiplicative interactions with elevated blood Pb levels or low plasma Se concentrations, which increased the ORs for CKD (p-values = 0.005 and 0.009, respectively). Our study is the first to show a significant interaction between plasma MPO concentration and metals affecting the OR of CKD.